2021
DOI: 10.1007/s00520-021-06386-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing pain in long-term survivors of childhood cancer

Abstract: Many long-term survivors of childhood cancer (LTSCCs) experience late-and long-term effects from their treatments, including pain. Yet, pain is poorly understood among LTSCCs. The current study aims to 1a) identify rates and patterns of chronic pain 1b) describe multiple dimensions of pain, and 2) test predictors of chronic pain in LTSCCs. Survivors [n=140; 48.6% male, Mage=17.3 years (SD=4.9)] were recruited from across Canada. Participants completed the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…In 2 previous studies, 47% of youth SCCs reported pain during at least 1 clinic visit 8 and 26% reported chronic pain that had lasted 3 months or longer. 7 Survivors of childhood cancers who experience persistent and frequent pain are likely those who have the greatest clinical need for pain relief and pain management.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 previous studies, 47% of youth SCCs reported pain during at least 1 clinic visit 8 and 26% reported chronic pain that had lasted 3 months or longer. 7 Survivors of childhood cancers who experience persistent and frequent pain are likely those who have the greatest clinical need for pain relief and pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Parents (or primary caregivers, herein referred to as parents) had to have a child meeting the above criteria and be able to read and understand English. Further information on the larger studies is outlined elsewhere 17–19 . All children and parents provided written informed consent or assent prior to participation.…”
Section: Methodsmentioning
confidence: 99%
“…Further information on the larger studies is outlined elsewhere. [17][18][19] All children and parents provided written informed consent or assent prior to participation. Ethics approval was obtained at all sites (IWK: #1023720, Alberta Children's Hospital: #HREBA.CC-17-0059, and Stanford University School of Medicine: #44463).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…[29][30][31][32] The United States alone counts over 420,000 childhood cancer survivors, 33 representing a unique and growing population of young people in need of long-term clinical support. 34 Studies suggest that 11%-43.9% of long-term childhood cancer survivors experience chronic pain, 35,36 defined as pain in one or more anatomic regions persisting or recurring for >3 months. 37 A report of 10,012 survivors from the Childhood Cancer Survivor Study (CCSS) 38 showed that 29% of long-term survivors of childhood cancer report moderate to severe pain, 20% report moderate to extreme pain interference, and 9% report moderate to severe recurrent pain.…”
Section: Pain Can Persist After Childhood Cancer Treatment Endsmentioning
confidence: 99%